Community Empowerment Strategy to Encourage Involvement in Subdistrict Organizations: An Overview in the Tingkir Tengah Subdistrict Area, Salatiga City - Nikolaus Rama Saputra; Runtunuwu, Brillian; Diva Jesika Febriana Lubis; Tegar Yudha Lesmana; Ira Alvanti Lambangasi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research focuses on efforts to empower the community in Tingkir Tengah, especially in the context of the SUPER TANGGUH Quality Family Village (KB). The aim of this program is to improve family welfare with a holistic approach, including sustainable economic, social, cultural and environmental aspects. There are six main objectives in this program, namely improving quality of life, welfare, harmony in the family, active community participation, environmental awareness, and improving infrastructure. By involving various groups such as Family Development for Toddlers, Teenagers, the Elderly, Youth Information and Counseling Center, and Efforts to Increase Prosperous Family Income, Kampung KB SUPER TANGGUH manages RT and RW using Rumah DataKu technology and Group Work Initiatives (POKJA). This structured data supports program management more efficiently. Apart from providing an overview of Tingkir Tengah Subdistrict, it is hoped that this research can become an example of an effective empowerment model to increase community participation and welfare at the subdistrict level